#TITLE_ALTERNATIVE# - BOBY WAHYU GUNARSO , DAMIANUS
The coastal region is an area between terrestrial and marine ecosystems which are affected by the change on land and sea. These changing are affected by coastal dynamics. Coastal dynamics, conceptually, due to three factors: physical (ocean dynamics), non-physical (social economy), and the characteristics of the beach itself, which occurs periodically and continuously. The purpose of this thesis is to observe coastal dynamic of Gembong estuary district and the effects of coast line changing, performed by modeling and measurement of current and tidal. This modeling performed by the method of hydrodynamic modeling using Delft3D software. In the early stages, the sensitivity models are performed to test and determine the model input of parameters. The sensitivity models are performed by inserting the three parameters, namely wind, seabed roughness with different levels of Chezy value, and the time step. Then simulation modeling for two seasons, namely West monsoon and East monsoon. From this modeling, the movement of flow velocity and tidal wave were analyzed for the observation of coastal dynamics on shoreline changing at the Gembong Estuary. Sensitivity models demonstrated the seabed roughness parameter most influence on the model results compared to the wind and the time step input parameters, with a value of Chezy 75, the maximum flow velocity occurs at 1.111 m / s. For the simulation of two seasons, the movement of the maximum flow velocity is when the West monsoon at 0.399 m / s, where as the movement of the maximum flow velocity East monsoon which occurs at 0.429 m / s. Meanwhile the value of the tide in west monsoon is 0.429 m and in east monsoon itÃ‚Â’s 0.452 m.based on the results of the model that has been done, flow movement in the Gembong Estuary District is influenced by the degree of seabed roughness and the East monsson.